ROS, autophagy, mitochondria and cancer: Ras, the hidden master? - Bellot, G.; Liu, D.; Pervaiz, Shazib (Elsevier, 2013)
Recent advances have highlighted the complex web of biological mechanisms and pathways involved in oncogenic transformation and maintenance of the cancer phenotype. To that end, a number of key factors have been identified and thoroughly investigated over the past couple of decades, such as redox regulation of cell fate decisions, cellular metabolism and bioenergetics, autophagy induction as a survival signal, and how these pathways interplay with oncogene-induced transformation. This has been particularly well documented for oncoprotein Ras-induced carcinogenesis, and recent reports provide ample evidence to indicate a well-coordinated crosstalk between these diverse cellular pathways in the process of cancer initiation and progression. Here we provide a brief summary of the recent advances in the field to illustrate the dual role of autophagy as a tumor suppressor and as a survival mechanism required for cancer maintenance as well as its implication in the complex relationship between Ras-mediated carcinogenesis, mitochondrial metabolism, cellular redox status and bioenergetics. © 2012 Elsevier B.V. and Mitochondria Research Society.